Development of Student Worksheet (LKPD) In Learning to Write Explanatory Texts With Contect Social Students in Grade VI of Elementary School 397 Padang Laru, East Panyabungan, Mandailing Natal - Sarifah, Siti; Sutikno (International Journal of Educational Research Excellence (IJERE), 2025)
The problem in this research is how appropriate are the LKPD (student worksheet) teaching materials in learning to write explanatory text with social content for class VI students, which were developed based on media experts, material experts, teachers and students? The aim of this research is to describe the suitability of LKPD (Students' Worksheets) teaching materials in learning to write explanatory texts with social content for elementary/MI students. The research method used in this research is the research and development method (Research & Development). The research subject for this product development is the validator. The research subject for this product development is the validator. The assessment is carried out by filling in the validation sheet provided, the validator in this research is the supervisor. Apart from that, the subjects of this research were class VI students at SD Negeri 397 Padang Laru. The object of this research is the Student Worksheet (LKPD) in learning to write explanatory texts with social content for class VI students at SD Negeri 397 Padang Laru. The instruments used to obtain research data use non-test instruments and test instruments. The results of this research indicate that Student Worksheets (LKPD) are suitable for use in improving explanatory text writing skills by class VI students at SD Negeri 397 Padang Laru, Kab. Mandailing Christmas for the 2024-2025 Academic Year. Apart from that, the results of testing LKPD (Students' Worksheets) teaching materials in learning to write explanatory texts with social content in class VI of SD Negeri 397 Padang Laru, Kab. Mandailing Natal for the 2024-2025 Academic Year shows that before the LKPD development process it was in the adequate category and then increased to good after the LKPD development process in class VI of SD Negeri 397 Padang Laru, Kab. Mandailing Christmas for the 2024-2025 Academic Year